PENGEMBANGAN MULTIMEDIA BERBASIS ANDROID UNTUK MENINGKATKAN PRESTASI BELAJAR PKN PESERTA DIDIK KELAS VII SMP REJANG LEBONG - Rita Apriyani; Buyung Buyung (DIADIK, 2022)
The purpose of this study is to describe: (1) Learning media with Android-assisted multimedia applications are feasible to improve student achievement. (2) The effectiveness of learning media with Android-assisted multimedia applications in improving student achievement. In this study used a development design (Research and Development). The research subjects were students of class VII SMP. Data collection techniques used in the study were assessment sheets and student test results. Analysis of the data in this research with the mean (mean) and t-test. The instrument for validation of media and materials and IT experts in this research is the Likert Scale. The conclusions of this research are; (1) Learning media with an android-assisted worked example application developed is feasible to improve student achievement in learning PPKN. (2) The development of learning media using the Android-assisted worked example application can improve student achievement based on the results of a limited trial and broad-scale test for class VII students of SMP N 2 Rejang Lebong